2012
DOI: 10.1002/uog.11168
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory enlargement of a solitary functioning kidney during fetal development

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 21 publications
1
23
0
Order By: Relevance
“…Compensatory enlargement of the single kidney in cases of URA during development has not been studied extensively . Hartshorne et al performed a retrospective analysis of 20 fetuses with isolated URA detected at autopsy.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Compensatory enlargement of the single kidney in cases of URA during development has not been studied extensively . Hartshorne et al performed a retrospective analysis of 20 fetuses with isolated URA detected at autopsy.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies assessing compensatory growth of the solitary kidney referred to mixed population of URA and MCDK, while in all studies, the former diagnosis contributed the minority of cases. Since these two entities are a result of different mechanisms leading to aberrant renal development that may in turn trigger a varying compensatory growth programme in the contralateral normal kidney, their compensatory growth curves should be studied separately.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals born with a solitary functioning kidney are presumed to have a congenital nephron deficiency but the time course over which functional and structural adaptations occur is less well understood. In human fetuses, between gestational ages of 20–36 weeks, 11% increase in the volume of the solitary kidney has been observed in almost 90% of fetuses . This increase in size of the solitary kidney is likely due to both hyperplasia and hypertrophy.…”
Section: Congenital Nephron Deficiency: Functional and Structural Adamentioning
confidence: 99%
“…In this setting, each nephron may have normal dimensions with subnormal single perfusion and filtration, and the risk of glomeruli injury would be proportionately reduced. Unfortunately, in these studies (9)(10)(11), nephron number was not reported. Prevalence of unilateral renal agenesis has been reported in 0.48-0.58 per 1,000 live births (12); a 13% decrease in renal function and a 47% increase in hypertension incidence have been reported in adult patients with unilateral agenesis (13).…”
mentioning
confidence: 99%
“…Moreover, kidney ultrasound studies performed during gestation show that the renal compensation begins before birth (11). In contrast to the adult, as nephrogenesis is not complete before 36 wk of gestation, enlargement of the remaining kidney could involve the formation of new nephrons.…”
mentioning
confidence: 99%